Experiences of Freelancers with AI and Chatbots - Eslami, Fereydon; Hooshmandi, Roodabeh (AI and Tech in Behavioral and Social Sciences, 2023)
This study aims to explore the experiences of freelancers with AI chatbots, identifying the main drivers behind their adoption, the challenges faced during their integration, and the overall impact on work and personal perceptions. Employing a qualitative research design, this study conducted semi-structured interviews with 29 freelancers from various professional backgrounds. Thematic analysis was utilized to distill the data into meaningful themes and categories, providing insights into freelancers' interactions with AI chatbots. Five main themes were identified: Adoption Drivers, Technological Challenges, Impact on Work, Ethical and Social Issues, and Personal Experiences and Reflections. Key findings include the efficiency gains and improved quality of work as primary adoption drivers, significant technological challenges related to integration and reliability, and varied impacts on job opportunities and financial aspects. Ethical concerns, notably regarding privacy, security, and bias, were prevalent. Personal reflections revealed a spectrum of perceptions on AI chatbots, from optimism about future prospects to concerns over professional identity and work-life balance. Freelancers' experiences with AI chatbots are marked by a complex interplay of benefits and challenges. While AI chatbots offer potential for efficiency and competitive advantage, their integration is hampered by technological hurdles and ethical dilemmas. Addressing these challenges, while fostering an environment that supports continuous learning and adaptation, is crucial for leveraging AI chatbots' full potential in freelancing.